2021
DOI: 10.14207/ejsd.2021.v10n1p339
|View full text |Cite
|
Sign up to set email alerts
|

Justice for Judges in Ukraine: Looking for Peace and Strong Judiciary Institutions in a Sustainable Society

Abstract: Regarding the judiciary, the purification and lustration initiatives had been alleged as a beginning of a new stage of radical reformation, appreciated by European institutions. Therefore, in this article we will provide a detailed picture of the lustration of judges in Ukraine from the angle of its procedural guarantees as well as its legal nature; a special focus will be given to issues of efficiency of lustration restrictions, provided by the national legislation as well as its compliance within the Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In our opinion, there are a number of factors that hinder Ukraine's transition to a digital economy, namely: lack of mutual exchange between the data of about 100 registers of Ukraine; lack of automated notary workplace; lack of remote authorization of clients with an electronic digital signature or ID-card; lack of legislative regulation for the creation of an electronic register of notarial acts and electronic notarial archive, lack of automatic creation of a notarial document; and a number of other technological gaps, which is responsible for servicing civil circulation. In addition, it should be borne in mind that all the above points, which are absent in our country, are available in most Latin notarial states, including post-Soviet countries (Rudenko et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, there are a number of factors that hinder Ukraine's transition to a digital economy, namely: lack of mutual exchange between the data of about 100 registers of Ukraine; lack of automated notary workplace; lack of remote authorization of clients with an electronic digital signature or ID-card; lack of legislative regulation for the creation of an electronic register of notarial acts and electronic notarial archive, lack of automatic creation of a notarial document; and a number of other technological gaps, which is responsible for servicing civil circulation. In addition, it should be borne in mind that all the above points, which are absent in our country, are available in most Latin notarial states, including post-Soviet countries (Rudenko et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In its decision, the ECtHR recalled that judicial officials have a duty to exercise restraint in exercising their freedom of expression in all cases where the authority and impartiality of justice may be called into question. 17…”
Section: The National Conception Of a Judge's Communicative Behaviourmentioning
confidence: 99%
“…On the other hand, the study identified the problematic nature of corruption and the lack of transparency in the functioning of the state apparatus. Another problematic aspect was the ambiguity of the legislation, which often leads to unclear distribution of powers and competencies between different levels of government (Rudenko et al, 2021).…”
Section: Introductionmentioning
confidence: 99%